Modlitwa Jezusa i Kościoła za Piotra (Łk 22,31-32) - Oktaba, Piotr (Verbum vitae, 2004)
The undertaken analysis of Lk 22,31-32 (in relation to Lk 9,28-36 and Acts 12,1-17) allowed us to perceive Peter, who is an example of intercessory prayer, meaning the unceasing and effective prayer of Christ for him (and all of his successors). This prayer, joined with the prayer of the Church, saves Peter (as well as every Christian), assists in his conversion and brings him back to the community. Peter felt the prayers of Christ and the Church, he gave witness to it, and in this way strengthened the faith of his brothers. Peter is a clear sign of the presence of Jesus in the Church the strength of His intercessory prayer.